DEREGULATION OF TFAM EXPRESSION PROMOTES MITOCHONDRIAL DAMAGE AND FIBROBLAST ACTIVATION IN SYSTEMIC SCLEROSIS - Zhou, Xiang; Trinh, Minh Thuong; Tran Manh, Cuong; Giessl, A.; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis - Zhou, Xiang; Trinh, Minh Thuong; Tran Manh, Cuong; Gießl, Andreas; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (Arthritis and Rheumatology, 2022)
Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin-induced skin fibrosis, bleomycin-induced lung fibrosis, and skin fibrosis induced by overexpression of constitutively active transforming growth factor beta type I receptor (TGF beta R Iota). Results TFAM expression was down-regulated in fibroblasts in SSc skin and in cultured SSc fibroblasts. The down-regulation of TFAM was associated with decreased mitochondrial number and accumulation of damaged mitochondria with release of mitochondrial DNA (mtDNA), accumulation of deletions in mtDNA, metabolic alterations with impaired oxidative phosphorylation, and release of the mitokine GDF15. Normal fibroblasts subjected to long-term, but not acute, exposure to TGF beta mimicked SSc fibroblasts, with down-regulation of TFAM and accumulation of mitochondrial damage. Down-regulation of TFAM promoted fibroblast activation with up-regulation of fibrosis-relevant Gene Ontology terms in RNA-Seq, partially in a reactive oxygen species-dependent manner. Mice with fibroblast-specific knockout of Tfam were prone to fibrotic tissue remodeling, with fibrotic responses even to NaCl instillation and enhanced sensitivity to bleomycin injection and overexpression of constitutively active TGF beta RI. TFAM knockout fostered Smad3 signaling to promote fibroblast activation. Conclusion Alterations in the key mitochondrial transcription factor TFAM in response to prolonged activation of TGF beta and associated mitochondrial damage induce transcriptional programs that promote fibroblast-to-myofibroblast transition and drive tissue fibrosis.
CRIS-Team WoS Importer:2022-04-15

X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic